ACUTE MYOCARDIAL INFARCTION SPECIFICS IN PATIENTS WITH CHRONIC TONSILLITIS - Kh. R. Dzhukaeva; Yu. G. Schwartz (Кардиоваскулярная терапия и профилактика)
Aim. To investigate the clinical specifics of acute myocardial infarction(AMI) in patients with chronic tonsillitis.Material and methods. The study included 70 patients at early AMI stages (Days 1–2). The following parameters were analysed: anthropometry, blood biochemistry, myocardial necrosis markers, QT interval dispersion, echocardiography and Holter ECG monitoring parameters, and a confirmed medical diagnosis of chronic tonsillitis in medical history.Results. In 31 patients with confirmed chronic tonsillitis, higher body mass index values, a significantly higher incidence of acute heart failure (19,4%; p<0,05) and anterior AMI (70%), higher glucose levels at admission (7,58±0,62 mmol/l), and a higher end-diastolic size of right ventriculum (3,04±0,19 cm vs. 2,66±0,05 cm) were observed. Mean daytime and peak nighttime heart rate values were higher than in other patients.Conclusion. Patients with confirmed chronic tonsillitis were characterised by a more severe clinical course of AMI. There is some evidence that chronic tonsillitis is also associated with metabolic syndrome.